Patatin‐like phospholipase domain containing 3 variants differentially impact metabolic traits in individuals at high risk for cardiovascular events. Issue 7 (6th June 2018) - Rüschenbaum, Sabrina; Schwarzkopf, Katharina; Friedrich‐Rust, Mireen; Seeger, Florian; Schoelzel, Fabian; Martinez, Yolanda; Zeuzem, Stefan; Bojunga, Jörg; Lange, Christian M.
Abstract : The PNPLA3 I148M is associated with hepatic fat accumulation, liver fibrosis and hepatocellular carcinoma. Here, we show that – likely as a consequence of hepatic fat accumulation – PNPLA3 I148M represents a risk factor for diabetes, but is inversely associated with serum cholesterol levels and the net risk for coronary artery disease. Abstract : Single nucleotide polymorphism (SNP) rs738409 C>G in the patatin‐like phospholipase domain containing 3 ( PNPLA3 ) gene results in an amino acid exchange from isoleucin to methionine at position I148M of PNPLA3. The expression of this loss‐of‐function mutation leads to impaired hepatocellular triglyceride hydrolysis and is associated with the development of liver steatosis, fibrosis, and hepatocellular carcinoma. In contrast to these well‐established associations, the relationship of the PNPLA3 rs738409 variant with other metabolic traits is incompletely understood. We therefore assessed the association of the PNPLA3 rs738409 genotype with relevant metabolic traits in a prospective study of patients at high risk for cardiovascular events, i.e., patients undergoing coronary angiography. In a total of 270 patients, known associations of the PNPLA3 rs738409 GG genotype with nonalcoholic steatohepatitis and liver fibrosis were confirmed. In addition, we found an association of the PNPLA3 rs738409 G allele with the presence of diabetes (22% versus 28% versus 58% for CC versus CG versus GG genotype, respectively; P = 0.02). In contrast to its association with nonalcoholic fatty liver disease, liver fibrosis, and diabetes, the minor G allele of PNPLA3 rs738409 was inversely associated with total serum cholesterol and low‐density lipoprotein serum levels ( P = 0.003 and P = 0.02, respectively). Finally, there was a trend toward an inverse association between the presence of the PNPLA3 rs738409 G allele and significant coronary heart disease. Comparable trends were observed for the transmembrane 6 superfamily member 2 (TM6SF2) 167 K variant, but the sample size was too small to evaluate this rarer variant. Conclusion : The PNPLA3 rs738409 G allele is associated with liver disease but also with a relatively benign cardiovascular risk profile. ( Hepatology Communications 2018;2:798‐806)